Algoritma Fuzzy Inference System sebagai Mitigasi Broadcast Storm pada Protokol Ad-Hoc On Demand Distance Vector (AODV) - Selma Aulia Sekarrizky; Reza Andria Siregar; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Mobile Ad-hoc Network (MANET) is a network without constantly infrastructure. MANET has a system that can manage itself from mobile nodes. Every nodes will find a routes sent from source nodes to destination nodes, this progress called routing. There are 3 category of routing protocols i.e. proactive protokol, reactive protocol and hybrid protocol. Ad-hoc On-Demand Distance Vector (AODV) is one of the example of reactive protokol. A routes will be formed if a nodes request for a transmission which is sent a route request packet (RREQ) from source nodes to destination nodes. if RREQ packets doesn't received by destination nodes or neighbors nodes, the source nodes will rebroadcast the RREQ packets until the destination nodes receive it and sent the route reply packets back with the same path. If it happens a lot, then flooding packets will occur. If flooding packets happens in a network, then congestion might happen and it called broadcast storm. Broadcast storm will impact redudancy packets, contention and collision. Fuzzy Inference System (FIS) is good for decision making case. So it can be a solution to mitigate broadcast storm. FIS will be used as Hello Interval specifier with network size and mobility as classification parameter. This research use nodes speed 0-10m/s and 0-5m/s as simulation parameters. The result is AODV with FIS and speed 10m/s has better result. AODV with FIS has lower routing overhead than original AODV for all nodes. AODV with FIS with speed 0-10m/s has 1% lower on nodes 150 and 200 which is in high category than original AODV. AODV with FIS with speed 0-10m/s has 12% and 8% higher on nodes 25 and 200 which is in low and high category.